A Comparison of Endoscopic Closure and Laparoscopic Repair for Gastric Wall Defection - Qiao Qiao; Huiming Tu; Bojian Fei; Kebin Xu; Fan Yang; Jie Li; Qizhong Gao (Gastroenterology Research and Practice)
Objective. To compare the effectiveness and safety of endoscopic closure and laparoscopic repair for gastric wall defection. Method. The clinical data of 120 patients with submucosal tumours enrolled at our hospital between January 2014 and December 2019 were retrospectively analysed. Patients were divided into two groups according to the surgery they underwent: an endoscopic closure group (n=60) and a laparoscopic repair group (n=60). The clinical characteristics, perioperative complications, and postoperative follow-up results of the two groups were analysed. Results. The surgery time in the endoscopic closure group was 56.20±11.25 minutes, which was significantly lower compared with that in the laparoscopic repair group (159.35±23.18 minutes; P<0.001). In addition, the postoperative stay in the endoscopic closure group was shorter than that in the laparoscopic repair group, and the intraoperative bleeding volume and incidence of enteral nutrition initiation after surgery were significantly lower. Medical expenses were also significantly lower in the endoscopic closure group than in the laparoscopic repair group (P<0.001). Only one patient developed a postoperative fever in the endoscopic closure group; three patients developed a postoperative fever and one patient had postoperative bleeding in the laparoscopic repair group. However, there were no statistical differences between the two groups regarding the incidence of R0 resection, postoperative fever, postoperative bleeding, and closure failure (all P>0.05). There were no local recurrences, distant metastases, or deaths in either of the groups during the two-year follow-up period. Conclusion. Non-laparoscopic-assisted surgery may be quicker, safer, and more effective for gastric wall defection.